Endometrial stromal cell miR-19b-3p release is reduced during decidualization implying a role in decidual-trophoblast cross-talk - Ellen Menkhorst; Ellen Menkhorst; Teresa So; Teresa So; Kate Rainczuk; Siena Barton; Siena Barton; Wei Zhou; Wei Zhou; Tracey Edgell; Evdokia Dimitriadis; Evdokia Dimitriadis; et al. (Frontiers in Endocrinology, 2023)
IntroductionA healthy pregnancy requires successful blastocyst implantation into an adequately prepared or ‘receptive’ endometrium. Decidualization of uterine endometrial stromal fibroblast cells (hESF) is critical for the establishment of a healthy pregnancy. microRNAs (miRs) are critical regulators of cellular function that can be released by a donor cell to influence the physiological state of recipient cells. We aimed to determine how decidualization affects hESF miR release and investigated the function of one decidualization regulated miR, miR-19b-3p, previously shown to be associated with recurrent pregnancy loss.MethodmiR release by hESF was determined by miR microarray on culture media from hESF decidualized in vitro for 3 and 14 days by treatment with oestradiol and medroxyprogesterone acetate. Cellular and whole endometrial/decidual tissue miR expression was quantified by qPCR and localized by in situ hybridization. The function of miR-19b-3p in HTR8/Svneo trophoblast cells was investigated using real time cell analysis (xCELLigence) and gene expression qPCR.ResultsFrom our miR screen we found that essentially all hESF miR release was reduced following in vitro decidualization, significantly so for miR-17-5p, miR-21-3p, miR-34c-3p, miR-106b-5p, miR-138-5p, miR-296-5p, miR-323a-3p, miR-342-3p, miR-491-5p, miR-503-5p and miR-542-5p. qPCR demonstrated that miR-19b-3p, 181a-2-3p and miR-409-5p likewise showed a significant reduction in culture media following decidualization but no change was found in cellular miR expression following decidualization. In situ hybridization localized miR-19b-3p to epithelial and stromal cells in the endometrium and qPCR identified that miR-19b-3p was significantly elevated in the cycling endometrium of patients with a history of early pregnancy loss compared to normally fertile controls. Functionally, overexpression of miR-19b-3p significantly reduced HTR8/Svneo trophoblast proliferation and increased HOXA9 expression.DiscussionOur data demonstrates that decidualization represses miR release by hESFs and overexpression of miR-19b-3p was found in endometrial tissue from patients with a history of early pregnancy loss. miR-19b-3p impaired HTR8/Svneo proliferation implying a role in trophoblast function. Overall we speculate that miR release by hESF may regulate other cell types within the decidua and that appropriate release of miRs by decidualized hESF is essential for healthy implantation and placentation.